A oralidade em O casamento de Nelson Rodrigues: um estudo das estratégias interacionais no diálogo - Oliveira, Fabiana Meireles de (2010)
The reason of search is investigate the fiction dialogue in romance of Nelson Rodrigues O casamento to examine how the strategy between races can motivate an integrate action between them. The focus of this analysis is the theory of analysis of conversation Is important to considerate the historical and geographic context of the character and the information extra linguistics supplied by the narrator to understand the characters and the situation of communication from where the dialogue is made. The dialogues analyzed in this search are considered like corpus of orally in the script because in the text there is dynamic dialogue, natural and authentic. We start of the hypothesis that romance s dialogue reveal naturalness and that the language of Nelson Rodrigues is like of language of situation face to face